Coalitional games with veto players: Myopic and rational behavior - J. Arin; V. Feltkamp; Maria Montero (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
This paper studies a noncooperative allocation procedure for coalitional games with veto players. The procedure is similar to the one presented by Dagan et al. (1997) for bankruptcy problems. According to it, a player, the proposer, makes a proposal that the remaining players must accept or reject. We present a model where the proposer can make sequential proposals over n periods. If responders are myopic maximizers (i.e. consider each period in isolation), the only subgame perfect equilibrium outcome is the serial rule of Arin and Feltkamp (2012) regardless of the order of moves. If all players are rational, the serial rule still arises as the unique subgame perfect equilibrium outcome if the order of moves is such that stronger players must respond to the proposal after weaker ones.
Keywords: C71; C72; C78; 330; veto players; noncooperative bargaining; myopic behavior; serial rule